2008
DOI: 10.1177/1089313x0801200104
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Lateral Ankle Sprain and Ankle Tendinitis in Ballet Dancers

Abstract: The lateral ligament complex of the ankle is the most frequently injured structure in the body. Although most simple ankle sprains do not result in long-term disability, a significant number do not completely resolve, leading to residual symptoms that may persist for years. The most commonly reported symptoms, particularly among athletes, include instability, re-injury and tendinitis. Ballet dancers are a combination of artist and high-performance athlete; consequently, they are subjected to the same types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 57 publications
1
3
0
8
Order By: Relevance
“…For example, our finding that the majority of injuries were due to overuse is consistent with the results of previous research [6-8, 14, 15, 24]. In addition, several previous studies have shown, in accordance with the results of the present study, that the most common site of injury is the foot and ankle region [8,14,15,24,32,35]. In contrast, some previous studies based on self-report found the spine to be the most common site of injury in ballet dancers [4,6,31].…”
Section: Discussionsupporting
confidence: 94%
“…For example, our finding that the majority of injuries were due to overuse is consistent with the results of previous research [6-8, 14, 15, 24]. In addition, several previous studies have shown, in accordance with the results of the present study, that the most common site of injury is the foot and ankle region [8,14,15,24,32,35]. In contrast, some previous studies based on self-report found the spine to be the most common site of injury in ballet dancers [4,6,31].…”
Section: Discussionsupporting
confidence: 94%
“…In the continuous training and performance of dancers, repeatedly jumping and landing as well as the extreme plantarflexion or rotation is required. During these dance movements, the repeated shocks and pressure will impact the injured area, and the commonly reported symptoms in dancers include ankle re-injury and instability [44]. All of the articles reviewed mentioned that wearing a pointe shoe and overuse on their foot may accelerate rates of muscle fatigue and ankle sprains [25,45].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the incidence of peroneal tendinosis and its correlation with lateral ankle instability has only been investigated in ballet dancers [27]. Peroneal tendinosis as a predisposing factor for ankle sprain trauma in runners has not been addressed so far.…”
Section: Discussionmentioning
confidence: 99%